Analysis of Traffic Performance and Passenger Car Equivalent Value in Tangerang – Merak Toll Road Section - Sidabutar, Jonathan; Soehodho, Sutanto; Nahry, Nahry (UI Scholars Hub, 2024)
Economic growth involves massive movement of logistics, where goods transported by land become the main choice by supplier. One of them being the main access for connecting Java and Sumatera is the Tangerang – Merak toll road. An increase in traffic volume occurs every year, followed by additional problems such as congestion which obviously affects traffic performance. Given this reason, it is necessary to evaluate traffic performance through parameter assessments, which are the degree of saturation and travel speed. This research was carried out on the Tangerang - Merak toll road section KM 32,300 to KM 35,500 towards Jakarta for one week using traffic CCTV recordings, then selected on 17 April 2024. The calculation results obtained for each average weighted value for the degree of saturation (Ds) at 0.36 and average of the Space Mean Speed is at 33.08 kph. Based on traffic performance analysis, the volume parameter does not indicate a problem, and is included in the LOS A category. However, the travel speed parameter shows an issue and included in the LOS F category. This will be the focus problem within the scope of the research. On the other side, traffic composition which includes variations in the number of vehicles per time and type of vehicle. Given this kind of variation, a Passenger Car Unit value is needed that can equalize the existing different vehicle types into a uniform standard, including who commit over dimensional violations. Where the value of passenger car equivalent of an over-dimensional vehicle is changing, it is necessary to re-calibrate the emp value. Researchers used the Volume Delay Function formula to calculate travel time, then explore a combination of emp values using the dynamic programming method by comparing survey travel time with the simulation one. The difference between the PKJI standard value and the calibrated pce value proves the problem of these vehicles commit over dimension violations on the Tangerang – Merak toll road. For this reason, it is hoped that this research which evaluate traffic performance, travel time and passenger car equivalent values, can be used as a basis for further policy making to improve the performance of the Tangerang – Merak toll road.